Circadian rhythm bifurcation induces flexible phase resetting by reducing circadian amplitude. (16th August 2018) - Noguchi, Takako; Harrison, Elizabeth M.; Sun, Jonathan; May, Deborah; Ng, Alan; Welsh, David K.; Gorman, Michael R.
Abstract: Shift‐work and jet‐lag–related disorders are caused by the limited flexibility of the suprachiasmatic nucleus (SCN), a master circadian clock in the hypothalamus, to adjust to new light–dark (LD) cycles. Recent findings confirmed here establish that behavioral jet lag after simulated time‐zone travel is virtually eliminated following bifurcated circadian entrainment under a novel and atypical 24‐h light:dark:light:dark (LDLD) cycle. To investigate the mechanisms of this fast resetting, we examined the oscillatory stability of the SCN and peripheral tissues in LDLD‐bifurcated mice employing the dissection procedure as a perturbing resetting stimulus. SCN, lung, liver, and adrenal tissue were extracted at times throughout the day from female and male PER2::Luciferase knock‐in mice entrained to either LDLD or a normal LD cycle. Except for adrenals, the phase of the cultured explants was more strongly set by dissection under LDLD than under normal LD. Acute bioluminescence levels of SCN explants indicate that the rhythm amplitude of PER2 is reduced and phase is altered in LDLD. Real‐time quantitative PCR suggests that amplitude and rhythmicity of canonical clock genes in the lung, liver, and kidney are also significantly reduced in LDLD in vivo. Furthermore, spatiotemporal patterns of PER2 peak time in cultured SCN were altered in LDLD. These results suggest that altered gene expression patterns in the SCN caused by bifurcation likely result in fast resetting of behavior and cultured explants, consistent with previously reported mathematical models. Thus, non‐invasive, simple light manipulations can make circadian rhythms more adaptable to abrupt shifts in the environmental LD cycle. Abstract : Jet lag in rodents can be virtually eliminated if previously adapted to two periods of light and dark per 24 h (LDLD). In mice under LDLD, the rhythmicity of clock genes is reduced, and clocks of tissues are strongly phase shifted by dissection procedures. These results suggest that rhythm bifurcation in LDLD reduces circadian amplitude, thereby rendering clocks of tissues more flexible to external stimuli. These results provide insights into new non‐invasive light therapies to reduce jet lag.